The future of food demand: A global meta-analysis and projections of income and price elasticities - Roche, Maxime; Comstock, Andrew; Ecker, Olivier (International Food Policy Research Institute, 2025)
Understanding how food demand responds to household income and price changes is essential for anticipating global food needs and designing effective food policies. Yet existing elasticity estimates vary widely due to differences in data, estimation methods, and study settings. This study aims to assess how empirical choices influence elasticity values and examine theory-based predictions related to income growth and inequality, urbanization, and demographic change. It provides the most comprehensive global systematic literature review and meta-analysis of income and price elasticities to date, compiling over 13,000 elasticity estimates from 215 peer-reviewed studies published between 1974 and 2022. We estimate two-level random effects meta-regressions and use the results to generate predicted elasticities for nine food groups by world region. While most data and methodological choices have little effect on price elasticity estimates, income elasticities are influenced by factors such as demand model type, use of conditional specifications, and the choice of expenditure measure. We find empirical support for Engel’s Law but only partial support for Bennett’s Law. Income elasticities are positively associated with urbanization, particularly in lower-income countries, and negatively associated with population aging. By projecting income elasticities through 2050 under alternative Shared Socioeconomic Pathways, we show that ignoring structural shifts in sociodemographics can yield meaningfully different estimates of future food demand.